Liquor in the land of the lost cause : southern white evangelicals and the prohibition movement - Coker, Joe L., 1969- (Religion in the South., 2007)
The temperance movement first appeared in America in the 1820s as an outgrowth of the same evangelical fervor that fostered a wide range of reform campaigns and benevolence societies. Like many of these movements, temperance was confined primarily to the northeastern United States during the antebellum period. Viewed with suspicion by Southerners because of its close connection to the antislavery movement, prohibition sentiment remained relatively weak in the antebellum South. In the decades following the Civil War, however, southern evangelicals embraced the movement with unprecedented fervor.